Pre-Service Teachers' Views on Cognitive Flexibility within the Scope of Teaching Practice - Hanife Esen Aygün; Çiğdem Şahin Taşkın (Anı Publishing, 2019)
This research aimed to examine the way pre-service teachers in Primary Education Department use their cognitive flexibility capacities within the scope of Teaching Practice and the way they use their cognitive flexibility capacities to solve the problems they encounter during their practice. The research was designed in descriptive phenomenology pattern. Data were analysed through using inductive content analysis technique. In this direction, four main categories were obtained. They are named as: "Teaching practice experience", "Believing in alternatives", "Using cognitive flexibility capacity" and" Contribution of teacher education".  Findings indicate that pre-service teachers encountered various difficulties during their Teaching Practice course and tried to overcome these difficulties. However, they did not find themselves as effective. Besides, a significant number of pre-service teachers find cognitive flexibility capacity important. Consequently, findings of this study will increase educators' as well as pre-service teachers' awareness of cognitive flexibility in teacher education, and thus contribute to the research in teacher education.